Staphylococcus aureus β-Hemolysin Up-Regulates the Expression of IFN-γ by Human CD56bright NK Cells - Guan, Zhangchun; Liu, Yu; Liu, Chenghua; Wang, Huiting; Feng, Jiannan; Yang, Guang (Frontiers in Cellular and Infection Microbiology, 2021)
IFN-γ is produced upon stimulation with S. aureus and may play a detrimental role during the infection. However, whether hemolysins play a role in the mechanism of IFN-γ production has not been fully characterized. In this study, it was demonstrated that Hlb, one of the major hemolysins of S. aureus, up-regulated IFN-γ production by CD56bright NK cells from human peripheral blood mononuclear cells (PBMC). In the further investigation, Hlb increased the calcium influx and then induced the phosphorylation of ERK1/2. Either blocking the calcium or inhibiting the phosphorylation of ERK1/2 with the specific inhibitors decreased the production of IFN-γ induced by Hlb. Moreover, we identified that this process was dependent on the sphingomyelinase activities of Hlb. Our findings revealed a novel mechanism of IFN-γ production in NK cells induced by Hlb, which may be involved in the pathogenesis of S. aureus.